Desorpsi Anion Klorida (Cl-) Dari Adsorben Silika Mesopori Template CTAB (Cetiltrimetilammoniumbromida) Termodifikasi Dimethylamine - Fadhilatu Zikra; Budhi Oktavia; Ananda Putra; Desy Kurniawati (Periodic, 2023)
Mesopore silica was prepared using sodium silica as a precursor and CTAB as a templating agent. However, silica has limitations in adsorption and desorption of chloride anions. Therefore, it is necessary to modify it to improve the action of mesopore silica. This study used DMA (dimethylamine) as a modifier with glycidoxypropyltrimethoxysilane (GPTMS) linking compound. Adsorption was carried out by injecting the adsorbate solution into the column containing the adsorbent at pH 7, and the optimum concentration was 20 mg/L. Furthermore, desorption was carried out by comparing the best desorption agents using acid desorption agents, namely nitric and sulfuric acids. The study showed that the percentage of nitrate desorption (95,29%)> sulfate (47,64%). After obtaining the best type of desorbing agent, desorption was carried out using nitrate with a concentration variation of (0,02; 0,04; 0,06; 0,08; 0,1) M. The optimum conditions for desorption of chloride anions on the modified mesoporous silica adsorbent were at 0,06 M.